Investigating the miRNA-mRNA interactome of human trabecular meshwork cells treated with TGF-β1 provides insights into the pathogenesis of pseudoexfoliation glaucoma - Anton W. Roodnat; Chelsey Doyle; Breedge Callaghan; Karen Lester; Megan Henry; Carl Sheridan; Declan J. McKenna; Colin E. Willoughby; Sarah D. Atkinson (PLoS ONE, 2025)
Pseudoexfoliation glaucoma is a severe form of secondary open angle glaucoma and is associated with activation of the TGF-β pathway by TGF-β1. MicroRNAs (miRNAs) are small non-coding RNA species that are involved in regulation of mRNA expression and translation. To investigate what glaucomatous changes occur in the trabecular meshwork and how these changes may be regulated by miRNAs, we performed a bioinformatics analysis resulting in a miRNA-mRNA interactome. Primary human trabecular meshwork cells originating from normal donors were treated with TGF-β1 at 5 ng/mL for 24h; total RNA was extracted followed by RNA-Seq and miRNA-Seq. For both mRNA and miRNA species, differential expression was determined using a bioinformatics pipeline consisting of FastQC, STAR, FeatureCounts, edgeR (for miRNA) and DESeq2 (for mRNA). Putative mRNA-miRNA interactions between differentially expressed mRNA and miRNA species were determined using interaction databases miRWalk, miRTarBase, TarBase and TargetScan. To classify mRNA species by function and pathway, gene enrichment was performed using Enrichr. The resulting miRNA-mRNA interactome consisted of 1202 interactions. Some highly connected microRNAs were hsa-let-7e-5p, hsa-miR-20a-5p, hsa-miR-122-5p, and hsa-miR-29c-3p. Most differentially expressed genes were indicated to be regulated by miRNAs. The sub-interactomes of genes involved in specific pseudoexfoliation glaucoma related enrichment terms such as oxidative stress, unfolded protein response, signal molecules and ECM remodelling were determined. This is the first study to present a genome-wide microRNA-mRNA regulatory network for human trabecular meshwork cells treated with TGF-β1 and may serve to generate unbiased hypotheses about regulatory functions and mRNA targets of miRNAs in pseudoexfoliation glaucoma and may help to develop miRNA-based therapeutics.